La metafora nell’Epistola Posteritati di Francesco Petrarca: Un approccio cognitivista - Boghiu, Maria (Verbum – Analecta Neolatina, 2018)
Metaphors have been long considered just some other figures of speech but this perspective has lately changed due to the cognitivist approach which considers the metaphor a fundamental tool of our conceptual system allowing abstract reasoning. In the light of this approach, I propose an analysis of the metaphors in Petrarch’s Letter to Posterity along with a picture of the conceptual schemes outlined by the text. This means both image-metaphors, which are still recognizable as figures of speech, and lexicalized-metaphors, in which the language user fails to perceive the metaphorical connections between the source-domain and the target-domain. The analysis of these connections is followed by a quantitative analysis, which allows us to recognize the most representative schemes and the most productive source domains. Besides that, a Latin text of a bilingual author allows us to follow the steps of a metaphorical expression in diachrony, that is, to check whether the expression is productive or not, and if it can be found in contemporary Romance languages, with a special focus on Italian.